2019
DOI: 10.1039/c9cp02703c
|View full text |Cite
|
Sign up to set email alerts
|

Large scale quantum dynamics investigations on the sensing mechanism of H2O, acetone, NO2 and O3 adsorption on the (MA)2Pb(SCN)2I2 surface

Abstract: The sensing mechanism of perovskite materials is described quantitively via bond breaking/formation and charge transfer analyses along with the dynamical processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…However, the weak Pb–I bonds in the structure are still the targets of oxidizing or reducing gases. It has been found that both the neutral H 2 O and oxidative gases (NO 2 , O 2 , and O 3 ) can form a stable Pb–O connection by directly attacking the Pb–I bonds . Anyway, in the study of the adsorption of reductive NH 3 by CH 3 NH 3 PbI 3 , it is found that the A-site CH 3 NH 3 + groups rapidly adsorb NH 3 and undergo H proton exchanges, thus blocking the interactions between the gas molecules and the skeletons; nevertheless, NH 3 can eventually break through the CH 3 NH 3 + barrier and interact with Pb to achieve stable adsorption and charge exchange.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the weak Pb–I bonds in the structure are still the targets of oxidizing or reducing gases. It has been found that both the neutral H 2 O and oxidative gases (NO 2 , O 2 , and O 3 ) can form a stable Pb–O connection by directly attacking the Pb–I bonds . Anyway, in the study of the adsorption of reductive NH 3 by CH 3 NH 3 PbI 3 , it is found that the A-site CH 3 NH 3 + groups rapidly adsorb NH 3 and undergo H proton exchanges, thus blocking the interactions between the gas molecules and the skeletons; nevertheless, NH 3 can eventually break through the CH 3 NH 3 + barrier and interact with Pb to achieve stable adsorption and charge exchange.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yamazoe et al, the initial move in the sensing process of semiconductor–gas molecules is to calibrate gas molecules and their active sites where the gas operates via the electronic changes introduced by gas–solid interactions. Our previous work , shows that the structural instability of the perovskite materials causes different dynamic changes around the adsorption sites. Such a property challenges the traditional static first-principles calculations; therefore, the quantum dynamics methodology is employed to deal with such special properties. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The theory plays a crucial role in investigating the several existing gas‐sensing mechanisms of semiconductor materials by applying first principle calculations [ 25–30 ] ; however, the instability of perovskite materials possibly induces the dynamic changes of adsorption patterns and active sites and reports on gas‐sensing mechanisms of organic–inorganic hybrid perovskite materials are rare. [ 31 ] Thus, it seems impossible to establish proper starting models for active sites and adsorption patterns of the gas molecules on the surface of the perovskite materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37,38 ] In the previous work, AIMD has been reported to accurately describe the distribution characteristics of gas molecules and structural change process of adsorbing materials during adsorption over a long time‐span. [ 31,39–43 ] In addition, it is also capable of describing the detailed process from reactants, then transient state to products during the adsorption reaction at the fs time‐scale and can show detailed changes in the reaction under the effect of surrounding environments in a complex system.…”
Section: Introductionmentioning
confidence: 99%